Midlatitude Synoptic Meteorology Dynamics, Analysis, and Forecasting - Lackmann, Gary.; SpringerLink (Online service) (Boston, MA : American Meteorological Society : Imprint: American Meteorological Society, 2011)
The past decade has been characterized by remarkable advances in meteorological observation, computing techniques, and data-visualization technology. Mesoscale Synoptic Meteorology links theoretical concepts to modern technology and facilitates the meaningful application of concepts, theories, and techniques using real data. As such, it both serves those planning careers in meteorological research and weather prediction and provides a template for the application of modern technology in classroom and laboratory settings.
Introduction, Background, and Basics -- Quasigeostrophic Theory -- Isentropic Analysis -- The Potential Voriticty Framework -- Extratropical Cyclones -- Fronts -- Baroclinic Instability -- Cold-Air Damming -- Winter Storms -- Numerical Weather PRediction -- Weather Forecasting -- Manual Analysis.
Keywords: Geography; Meteorology; Earth Sciences; Meteorology/Climatology.; Atmospheric Sciences